The Role of Social Work in Empowering People Living with HIV (PLHIV) for Poverty Alleviation in the Huye District in Rwanda: Indigenisation and the Role of Intermediary Social Work Actors (Journal of Comparative Social Work, 2025)
People in need (PIN), such as people living with HIV/AIDS (PLHIV), are often discriminated against, isolated and disempowered. Consequently, it is not always easy for them to fight for their survival. However, the literature has shown that once empowered, PLHIV manage to cope with social problems, particularly poverty and its ramifications. This study aimed to examine and show how social work, as an empowering profession, has the potential to contribute to the mitigation of adversities, particularly poverty, that hinder the betterment of the lives of PIN. In particular, this study examined the phenomenon of social work indigenisation as a means of re-invigorating practice approaches by drawing on the case of Rwanda. This study is based on data collected in the Huye District for my PhD research project, which was completed in January 2023. The research adopted an exploratory sequential mixed-methods design, with great privilege given to the participatory action research (PAR) methodology. The research results showed that social workers are key catalysts, and are well positioned to empower PIN. For effective success, it is essential that they work with intermediary social work actors (ISWAs), and use mostly developmental approaches that should integrate indigenous practices. Ultimately, the findings of this study provide evidence that PAR is beneficial to the bridging role of ISWAs in the problem-solving process, and thus may be recommended to be adopted for adequately mitigating poverty.